EARNINGS MANAGEMENT: A LITERATURE REVIEW - Debbianita, Debbianita; Kuang, Tan M; Hoetama, Marcella (Indonesian Journal of Accounting and Governance, 2024)
Earning is an important component in financial statements that can be modified by managementpolicies. Managers have the opportunity to present profits according to their wishes because managershave more information so they are free to do this which is called earnings management. In our study, theresearchers attempt to review the literature studies that provide an analysis of earnings managementimpact from two perspectives. The researcher attempts to review existing research/literatures thatprovide an analysis of earnings management from two perspectives. The articles used in this studyconsist of 50 articles on earnings management that have been published in international journals andwere obtained from Google Scholar using the keyword "earnings management". The research findingsindicate that the majority of the articles are quantitative studies utilizing the accrual-based earningsmanagement approach and possess an opportunistic perspective towards earnings management.Research on earnings management has been extensively conducted, but only a few have exploredearnings management from a signal perspective. The study aims to examine two different point of viewfrom earnings management article.